Zatoichi in desperation [videorecording (DVD)] - Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Taichi, Kiwako, 1943-1992; Yoshizawa, Kyoko, 1954-; Shimozawa, Kan, 1892-1968 (AnimEigo, 2004)
"After a fatal encounter with an elderly woman on a decrepit rope bridge, Zatoichi seeks out her daughter, to make restitution for his role in her death. He finds that the daughter, Nishikigi, is the most popular prostitute in the local brothel. Vowing to save Nishikigi from this life of sin, he sets out to earn the money to redeem her. But the blind swordsman goes too far when he hustles the local yakuza gang for the money. Now, trouble comes from all sides as the local boss, a master swordsman and the prostitute's lover, all want a piece of Zatoichi. Worst of all, Nishikigi just can't seem to turn her back on her life of sin! All these lead to the most shocking of ends of Zatoichi, one which will leave him forever changed!"--Container. The 24th movie in the series.